Las formas de tratamiento en un corpus de entrevistas semidirigidas de español de Galicia - Sampedro Mella, María (2015)
This work is a study of address forms in the semi directive interview corpus belonging to PRESEEA - Santiago de Compostela - ES and to ESLORA. After an introduction regarding the sample of study selected for this research and a bibliographical synthesis about the status of address forms in Spanish, the results of the tú/usted uses are included, according to the influence of different social (inherent to the speakers) and contextual factors. From these results, a part of this work focuses on the qualitative study of an interesting aspect that was found in the analysis: the variation of tú/usted that happens in the presence of the same interlocutor along the same interview, due to different causes.